ROLES OF COMMUNITIES OF PRACTICE FOR THE DEVELOPMENT OF THE SOCIETY - MOHAJAN, Haradhan Kumar (Journal of Economic Development, Environment and People, 2017)
At present one of the most important concepts in social learning theory is the idea of communities of practice (CoP), which describes a learning theory with a strong relationship to the social construction of knowledge. A CoP is a collection of people who engage on performing a common activity for the welfare both of members of the community and the society. In modern society, it is used in some form of high levels of skills, knowledge and proficiency to perform the jobs properly. It plays an important role in the sharing of knowledge and creating value for both their members and organizations. A CoP is composed of three crucial characteristics: domain, community, and practice, which provide a guide to the development of community. The paper describes structural components, basic characteristics, and essential elements of a CoP. It also highlights benefits, importance, and the challenges and barriers of a CoP. In addition, it describes virtual CoP in brief. The main aim of this study is to explore the ins and out of a CoP in some details